2017
DOI: 10.1128/jvi.02462-16
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Adenoviruses Displaying Matrix 2 Ectodomain Epitopes on Their Fiber Proteins as Universal Influenza Vaccines

Abstract: Influenza is a zoonotic disease that poses severe threats to public health and the global economy. Reemerging influenza pandemics highlight the demand for universal influenza vaccines. We developed a novel virus platform using extracellular domain IV of the matrix 2 protein (M2e), AdC68-F3M2e, by introducing three conserved M2e epitopes into the HI loop of the chimpanzee adenovirus (AdV) fiber protein. The M2e epitopes were expressed sufficiently on the AdV virion surface without affecting fiber trimerization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…M2e is present on the virus' surface in low quantities and, thus, it is poorly immunogenic (Wu et al, 2007 ). However, strategies to improve immunogenicity, such as adjuvants, multimeric forms of M2e, co-immunization with other influenza vaccines, or fusion with carrier proteins (Kim et al, 2013 ; Lee et al, 2015 ; Tang et al, 2017 ) stimulate broad cross-reactive immune responses and provide protection against heterologous, hetorosubtypic challenge in mice (Lee et al, 2015 ; Tao et al, 2017 ). Human clinical trial demonstrated the safety and immunogenicityof different M2e vaccine candidates (reviewed in Turley et al, 2011 ; Kolpe et al, 2017 ).…”
Section: Efforts To Avert the Setbacks In Vaccine Usementioning
confidence: 99%
“…M2e is present on the virus' surface in low quantities and, thus, it is poorly immunogenic (Wu et al, 2007 ). However, strategies to improve immunogenicity, such as adjuvants, multimeric forms of M2e, co-immunization with other influenza vaccines, or fusion with carrier proteins (Kim et al, 2013 ; Lee et al, 2015 ; Tang et al, 2017 ) stimulate broad cross-reactive immune responses and provide protection against heterologous, hetorosubtypic challenge in mice (Lee et al, 2015 ; Tao et al, 2017 ). Human clinical trial demonstrated the safety and immunogenicityof different M2e vaccine candidates (reviewed in Turley et al, 2011 ; Kolpe et al, 2017 ).…”
Section: Efforts To Avert the Setbacks In Vaccine Usementioning
confidence: 99%
“…Epitopes from a variety of different pathogens have been tested (e.g. HIV‐1, influenza A, Plasmodium falciparum ). One group, for example, demonstrated that a multivalent HIV‐1 vector based on AdHu5 elicited antibody responses to an externally presented HIV‐1 B‐cell epitope, in addition to cellular response to the virally encoded HIV‐1 gag antigen .…”
Section: Enhanced Adenoviral Vectorsmentioning
confidence: 99%
“…Construction of vaccines based on the display of foreign epitopes in the VRs of the HAdV capsid proteins has been demonstrated to be a strategy that has the potential of eliciting a robust and protective immune response against epitopes of a wide variety of pathogens ( Farrow et al, 2014 ; Tang et al, 2017 ; Wu et al, 2015b ). Different HAdV genotypes have been used as prototypes to display foreign epitopes, and genotype HAdV-5 from species C is the most studied in the context of epitope display and anti-HAdV immune responses ( Vujadinovic and Vellinga, 2018 ).…”
Section: Introductionmentioning
confidence: 99%